Board Committee Overlap and the Use of Earnings in CEO Compensation Contracts - Carter, Mary Ellen; Lynch, Luann J.; Martin, Melissa A. (Management Science, 2022)
Using proxy statement data describing the terms of compensation contracts, we examine how overlapping membership between compensation and audit committees influences the use of earnings metrics in compensation. Although research predicts that such overlap could either increase or decrease the reliance on earnings, we find that firms with overlapping directors rely less on earnings-based performance measures in incentive contracts without altering the overall level of performance-contingent cash bonuses. In addition, we provide evidence that firms substitute earnings measures with measures less subject to earnings management. Our findings are robust to potential alternative explanations, extend to an implicit relation between earnings and compensation for a larger sample, and are not driven by the tendency toward an overlapping committee structure more broadly. This paper was accepted by Suraj Srinivasan, accounting.